Transformation of Health Services in 3T (Frontier, Outermost, and Underdeveloped areas) Regions: Integration of Organizational Capabilities and Community-based Collaborative Governance Models in Raja Ampat Regency - Meokbun, Petrus (KnE Social Sciences, 2025)
The 3T regions (frontier, outermost, and underdeveloped areas) in Indonesia face significant challenges in delivering equitable and quality healthcare services. Raja Ampat Regency, as an archipelagic region in Southwest Papua, represents a clear example of these issues. This article aims to analyze the transformation of healthcare service models by integrating organizational capabilities and community-based collaborative governance. Using a qualitative case study approach, this research explores the internal dynamics of healthcare organizations and the role of local actors in building a collaborative ecosystem. The findings reveal that strengthening adaptive organizational capacity, enhancing community involvement, and fostering cross-sector synergy are key to developing responsive and sustainable healthcare services. These insights contribute to the development of contextualized healthcare models for 3T regions.